Pola Komunikasi Kelompok Santri Putri Dalam Penanganan Masalah Internal di Pondok Pesantren Bahrul Amiq Ngawi - Arifa Rahma, Zahwa Zanuba; Riyanto, Buddy; Sihabuddin, Sihabuddin (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
This study aims to describe and analyze the group communication patterns of femalesantri in dealing with internal problems at the Bahrul Amiq Ngawi Islamic Boarding School.This research uses a qualitative method with a descriptive approach. Data were collectedthrough field observations and in-depth interviews with female santri. The results showed thatthe communication patterns applied include downward communication, upwardcommunication, horizontal communication, and informal communication. Downwardcommunication plays a role in conveying instructions and goals from administrators to santri,while upward communication allows santri to provide feedback and suggestions toadministrators. Horizontal communication is used for coordination between fellow students,supporting effective cooperation, and strengthening relationships between them. In addition,informal communication proves to be an important tool in strengthening emotional bonds andaccelerating information dissemination. Despite obstacles such as differences in backgroundand age, the right communication approach succeeds in minimizing conflicts and increasingharmony and discipline in the pesantren environment. In conclusion, the application of diverseand adaptive communication patterns in Pondok Pesantren Bahrul Amiq Ngawi not onlysupports the handling of internal problems, but also contributes to the holistic characterbuilding and spiritual development of santri.Keywords: Communication patterns, Internal problems, Deliberation, Female santri,Boarding school